A conceptual analysis of the relationship between the personal identity and the changes of the brain - Rynkiewicz, Kazimierz (Hybris, 2012)
This essay aims to show that philosophy-hence also ethics-and neuroscience are dependent on each other. To make this visible, is to investigate the relationship between the personal identity and the changes of the brain. While the personal identity still owes its scientific resonance of philosophy, the brain is one of the entities that neuroscience is responsible to analyze in the first place. These three perspectives have to be taken into account: mereological, hermeneutic, and concrete.